Effects of Palm-Oil-Based Methyl Ester Sulfonate (MES) in Laboratory-Scale Enhanced Oil Recovery Process - Ridaliani, Onnie; Samsol; Setiati, Rini; Fathaddin, Muhammad Taufiq; Anggela, Lilian; Prima, Andry; Davy, Nandito; Yanti, Widia (Scientific Contributions Oil and Gas, 2025)
Natural Declining oil production is often caused by reduced natural driving forces within reservoirs. To address this limitation, enhanced oil recovery (EOR) technology introduces external energy or chemical agents to mobilize residual oil. This study evaluated the performance of palm-oil-based methyl ester sulfonate (MES) an anionic and biodegradable surfactant synthesized from renewable feedstock for improving recovery efficiency under laboratory-scale conditions. Core-flood experiments were performed using Berea sandstone cores, intermediate 33°API crude oil, low salinity of 10,000 ppm, synthetic brine at 60 °C. The testing sequence included screening test of palm-oil-based MES, brine saturation, oil saturation, waterflooding, and subsequent surfactant flooding with 1.5% MES solution. During waterflooding, the recovery factor reached 62.8 %, leaving 31.29 % residual oil saturation. Injection of 1.5 wt % MES increased the recovery factor to 68.8 % and reduced residual oil saturation to 26.25 %, indicating enhanced displacement and improved microscopic sweep efficiency. The results confirmed that palm-oil-derived MES effectively mobilizes trapped oil and demonstrates strong potential as an environmentally friendly and locally available surfactant for chemical EOR applications in the reservoirs.